Writing measurable goals in an individual education plan - Chichevska Jovanova, Natasha; Dimitrova Radojichikj, Daniela (Faculty of Philosophy, Skopje, 2017)
Since every child is unique, there is no pattern or standard format for writing measurable goals in individual education plan (IEP). Even two or more children with similar difficulties or even in the same condition (for example, autism or ADHD), will learn, develop and progress differently, and therefore, they cannot share a common IEP. It is very important for the individual plan to be in compliance with the curriculums and organization in the school, as well as to be clearly written and easily applicable. There shouldn’t be many goals, and set goals should express the expected positive achievements, not the things that the student is not able to achieve. Also, it is very important to put focus on short-term and specific goals, and not to globalize with setting common goals. The child may have biggest problems during accomplishing educational goals, but that doesn’t mean that those goals should be realized first. It is common situation amongst children to starts school without previously adopted working habits, and in such case, the adoption of working habits is going to be the priority goal. If the child doesn’t fit well in the group, achieving cooperation and friendships with their peers would be the priority goal, and only afterwards transfer to educational goals. The answer of the question WHAT, WHEN and HOW is the student supposed to do is the basis of IEP’s goals determination. In this study we are going to present IEP for a student in IV grade, put stress on assessment of current level of functional performance, discover his strengths and weaknesses, pay attention to writing measurable goals and indicate the procedures for measuring development regarding the annual goals.
Keywords: individual education plan, goals, student, teacher